1996
DOI: 10.1006/viro.1996.0008
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus E7 Oncoproteins Bind a Single Form of Cyclin E in a Complex with cdk2 and p107

Abstract: The E6 and E7 proteins of the high-risk human papillomaviruses (HPVs) act coordinately to immortalize human keratinocytes. These viral oncoproteins function by binding and altering the activity of cellular proteins which regulate cell cycle progression. Among the proteins bound by E7 are the retinoblastoma protein, Rb, as well as the related p107 and p130 proteins. In addition, E7 binds cyclin A, which regulates transit through the S and G2/M phases of the cell cycle. In this study, we demonstrate that HPV 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
1
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 5 publications
4
87
1
4
Order By: Relevance
“…In addition our ®ndings suggest that this might be relevant for the ability of HPV16 E7 to transform cells. This is supported by our ®ndings that MPP2 can stimulate E7/Ha-Ras-induced colonies in REFs and that neither HPV6 E7 nor HPV16 E7 mutants impaired in transformation (Phelps et al, 1992;McIntyre et al, 1996) were able to stimulate MPP2-speci®c transactivation (Figures 6, 8 and 9). Importantly the chromosomal localization of MPP2 was recently mapped to 12p13 (Korver et al, 1997b).…”
Section: Discussionsupporting
confidence: 65%
“…In addition our ®ndings suggest that this might be relevant for the ability of HPV16 E7 to transform cells. This is supported by our ®ndings that MPP2 can stimulate E7/Ha-Ras-induced colonies in REFs and that neither HPV6 E7 nor HPV16 E7 mutants impaired in transformation (Phelps et al, 1992;McIntyre et al, 1996) were able to stimulate MPP2-speci®c transactivation (Figures 6, 8 and 9). Importantly the chromosomal localization of MPP2 was recently mapped to 12p13 (Korver et al, 1997b).…”
Section: Discussionsupporting
confidence: 65%
“…In vitro studies have shown that for high-risk HPV: i) the binding of E7 to Rb abrogates the G1/S checkpoint (Thomas et al, 1998); ii) HPV E7 binds cyclin A and E (McIntyre et al, 1996) resulting in prolonged S phase or S phase arrest; and iii) E7 inhibits cyclin E-associated kinase and up-regulates cyclin A (Schulze et al, 1998). These observations are consistent with our findings in low-grade SIL.…”
Section: Discussionmentioning
confidence: 99%
“…Cip1 and causes a deregulated expression of cyclin E (McIntyre et al, 1996;Martin et al, 1998) thereby creating an aberrant S phase-like state that supports viral replication (Munger et al, 2001). How these activities can trigger centriole overduplication within a time period that corresponds to approximately a single cell-division cycle (Duensing et al, 2004(Duensing et al, , 2006a in currently unknown.…”
Section: Introductionmentioning
confidence: 99%